Carnosic Acid Protects INS-1 β-Cells against Streptozotocin-Induced Damage by Inhibiting Apoptosis and Improving Insulin Secretion and Glucose Uptake - Waseem El-Huneidi; Shabana Anjum; Mohamed A. Saleh; Yasser Bustanji; Eman Abu-Gharbieh; Jalal Taneera (Molecules, 2022)
Carnosic acid (CA), a natural polyphenolic diterpene derived from Rosmarinus officinalis, has been proven to possess a broad spectrum of medicinal properties. Nevertheless, no studies on its impact on pancreatic β-cells have been conducted to date. Herein, clonal rat INS-1 (832/13) cells were pretreated with CA for 24 h and then incubated with streptozotocin (STZ) for 3 h. Several functional experiments were performed to determine the effect of CA on STZ-induced pancreatic β-cell damage, including cell viability assay, apoptosis analysis, and measurement of the level of insulin secretion, glucose uptake, malondialdehyde (MDA), reactive oxygen species (ROS), and proteins expression. STZ treatment decreased cell survival, insulin secretion, glucose uptake, and increased apoptosis, MDA, and ROS production in INS-1 cells. Furthermore, protein expression/phosphorylation analysis showed significant down-regulation in insulin, PDX-1, PI3K, AKT/p-AKT, and Bcl2. On the other hand, expression of BAX and BAD and cleaved PARP were significantly increased. Interestingly, preincubation with CA reversed the adverse impact of STZ at the cellular and protein expression levels. In conclusion, the data indicate that CA protects β-cells against STZ-induced damage, presumably through its modulatory effect on the different pathways, including the Pi3K/AKT/PDX-1/insulin pathway and mitochondria-mediated apoptosis.